The role of cardiac surgeons in online prenatal counselling for congenital heart disease. Issue 10 (October 2019) - Zhu, Yaobin; Zhang, Yaping; Ding, Nan; Zhao, Yudong; Ye, Zankai; Fan, Xing; Liu, Yang; Shen, Lei; Yi, Hanlu; Li, Zhiqiang
Objective: To explore the role of cardiac surgeons in prenatal online counselling for congenital heart disease. Methods: From January 2014 to December 2017, the author consulted on 400 cases of foetal cardiovascular abnormalities through the Good Doctor Online and WeChat online platforms. The author made appropriate pregnancy recommendations to patients and families using patient ultrasound reports and medical histories. Followed-up patients who chose to continue their pregnancy received postnatal advice. Results: There were 248 simple cardiac abnormalities and 152 complex cardiac abnormalities. Foetal chromosome examination detected 2 cases of trisomy 21 syndrome and 26 normal cases. Two mothers (0.8%) of simple cardiac abnormality foetuses and 103 (67.8%) mothers of complex cardiac abnormality foetuses chose induced abortion. A total of 246 mothers of simple cardiac abnormality foetuses chose to continue pregnancy and had good postnatal prognosis. Twenty-six mothers of complex cardiac abnormality foetuses chose to continue pregnancy; among these, there were 4 intrauterine deaths, 22 births, 4 deaths while awaiting surgery and 18 successful surgeries. Conclusion: The Good Doctor Online and WeChat platforms facilitate communication with a wide audience. Cardiac surgeons can reduce the birth incidence and improve prenatal consultations for severe congenital heart disease through these platforms.